2018
DOI: 10.3198/jpr2017.12.0086crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Four Postflowering Drought‐Tolerant Grain Sorghum Lines with Early‐Season Cold Tolerance

Abstract: Four sorghum (Sorghum bicolor L.) germplasm lines-PSLS-SGCTB01 (Reg. No. GP-842, PI 685009), PSLS-SGCTR02 (Reg. No. GP-843, PI 685010), PSLS-SGCTB03 (Reg. No. GP-844, PI 685011), and PSLS-SGCTB04 (Reg. No. GP-845, PI 685012)were developed by the USDA-ARS in Lubbock, TX. The primary purpose for the release of these lines is to provide an alternative germplasm choice with superior early-season cold tolerance stacked with postlowering drought tolerance based on the stay-green trait. The PSLS-SGCTB01 and PSLS-SGCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For example, sorghum growers in Ethiopia and Burkina Faso indicated that severe drought during post-flowering stages is a major sorghum production constraint (Ouedraogo et al 2017 ; Derese et al 2018 ). Similarly, Burke et al ( 2018 ) reported that drought stress during the post-flowering growth stage had drastic effects on sorghum productivity due to premature plant death and reduced seed size (Burke et al 2018 ). A classical study over a period of 2 years involving 30 sorghum cultivars showed that drought stress during post-flowering stage reduced grain yield by about 50% (Batista et al 2019 ).…”
Section: The Effect Of Drought Stress On Sorghum Grain Yieldmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, sorghum growers in Ethiopia and Burkina Faso indicated that severe drought during post-flowering stages is a major sorghum production constraint (Ouedraogo et al 2017 ; Derese et al 2018 ). Similarly, Burke et al ( 2018 ) reported that drought stress during the post-flowering growth stage had drastic effects on sorghum productivity due to premature plant death and reduced seed size (Burke et al 2018 ). A classical study over a period of 2 years involving 30 sorghum cultivars showed that drought stress during post-flowering stage reduced grain yield by about 50% (Batista et al 2019 ).…”
Section: The Effect Of Drought Stress On Sorghum Grain Yieldmentioning
confidence: 99%
“…These results suggest that interaction between drought and other abiotic stresses is complex, particularly under natural conditions as it involves several factors. However, the presence of sorghum genotypes that are tolerant to drought and other abiotic stresses (Burke et al 2018 ) indicates the possibility of developing cultivars combining these important traits.…”
Section: Combined Effects Of Drought Stress and Other Major Biotic And Abiotic Factors On Plant Growth And Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PSLS‐CTB06, PSLS‐CTR07, PSLS‐CTR08, PSLS‐CTB09, and PSLS‐CTB10 exhibited greater final percentage germination than did the cold‐tolerant controls, none of these lines had germination percentages as good as PSLS‐SGCTB04 (JB15). PSLS‐SGCTB04 (JB15) is a line that we recently released having both cold tolerance and the stay‐green trait (Burke et al, 2018).…”
Section: Characteristicsmentioning
confidence: 99%